Theoretical and experimental investigations on fracture statistics carried out at the IDIEM (Chile) - P. Kittl; G. Díaz; M. León (Materiales de Construccion, 1986)
The high exigencies required for some structures owing to their responsability or their high cost have originated a new discipline that can be called Reability Engineering, which main aim is to determine the probability afforded by a machine to comply a requirement. This work contains a not fully detailed description of the topics studied by IDEM during those last years, within this field. Within it there are Fracture Statistics, which studies the probability for some structure to undergo plastic deformations, and the probability of the causes to occur, taken into account materials fatigue. It also includes a theoretical development of the fracture statistics, describing the specific-risk-of-fracture functions by means of integral equations, and the determination of their parameters and their uncertainties, when the functions have a known analytical form. Experimental researches range from the most brittle bodies, such as glass, almost brittle ones such as cement paste and to others that can admit plastic deformation, such as certain weldings, enlarging the study to fibro-composites and natural materials such as granite.